Desarrollo del talento humano como factor clave para el desarrollo organizacional, una visión desde los líderes de gestión humana en empresas de Bogotá D.C. - Claudia Esmeralda Pardo Enciso; Olga Lucia Díaz Villamizar (Suma de Negocios, 2014)
Organizational development has been a movement that emerged after 1962 as an educational mechanism that attempts tomodify the structures, beliefs and values of individuals within organizations, since the groups are inevitably subject to a process of rapid change in all areas (College of Bachelors, 2005). Moreover, this is the result of organizational change that emerges froman identified need, which occurs in the interest of changing a management strategy focused on processes or goals, improve organizational climate, transform culture, and reduce the impact of processes of division or business fusion and among other aspects, the effective participation of its members in organizational goals. It is for this reason that the role of human capital in all processes of organizational change is framed within a analysis vision, anticipate and potentiate behavior, as well as internaldynamic relations, knowledge and the what to make of people in context. The main purpose of this study is to understand how the processes of training and competences development became key to the organizational transformation in companies in Bogotá City, from the viewpoint of the leaders of Human Resources managers. The methodology is based on an exploratory - descriptive study with a co relational goal as it seeks to reach even better understanding of the phenomenon being studied. To this end the design and implementation was performed through the design and application of semi-structured interviews and surveys as tools for data collection, by which intentional results sampled 81 companies in Bogotá that developed models for staff development. The expected result is to identify how these programs have become a key factor for organizational development.